SEXUAL ABUSE SCANDAL AND ITS IMPLICATIONS FOR SEMINARY FORMATION - Mathias, Gabriel (Asian Horizons, 2020)
According to research on the crisis of clerical abuse of minors in the Catholic church, especially the report of the John Jay College Research Team (2011), The Causes and Context of Sexual Abuse of Minors by Catholic Priests in the United States, defective human formation in seminaries contributed to the crisis. The article deals with ways of remedying the situation proposing suggestions for integrated celibate living and supports for achieving celibacy. Specific to paedophilia, there are details of the red-flags and warning signs that the formators need to pay attention to, as well as ways to address intimacy deficits, boundary violations and stress points in ministry which can trigger abuse.